The relationship between attitudinal constructs and UTM students’ intention to adopt mobile learning - Siti Fariza Mat Sapri, author 611993 (Johor Bahru, Johor : Universiti Teknologi Malaysia, 2018)
Project Paper (Sarjana Muda Pengurusan (Teknologi)) - Universiti Teknologi Malaysia, 2018